A Review Study to Assess Skirted Foundation's Performance - Rawaa Rafea Khudhair‎; Bushra Suhale Albusoda (Journal of Engineering)
Innovative structural supports, known as skirted foundations, are primarily employed in offshore engineering. Skirted foundations extend below the footing like conventional shallow foundations and carry loads to deeper soil layers. A "skirt" is a wall that surrounds the foundation from one side or more, is connected to the foundation, and functions as a single unit. These skirts are essential for improving overall stability and transferring loads to more stable subsurface layers, which improves the foundation's performance.  Significant features of skirted foundations make them promising for economics and appropriate for use in constructions with large loads and poor soil conditions. It has been demonstrated that skirted foundations are a more effective alternative to conventional foundations like piles, piers, etc. It is regarded as economical because of the reduction of employing building materials, less machinery, and a smaller workforce, as well as the saving of time necessary for installation. This review paper summarizes previous experimental and numerical investigations on skirted foundations and surveys their characteristics; the important conclusions can be summarized: The ratio of skirt length to foundation width (2) gave the best results in improving bearing capacity and minimizing settlement. The ultimate load increased when the skirt inclination increased from 10° to 30° because an attachment area was established between the inclined angle and the soil. Circular skirts can result in higher bearing capacity and lower settlement than square skirts when both are placed under comparable conditions. Also, skirted foundations are suitable for supporting shallow foundations in seismic zones.